PENGARUH GROWTH OPPORTUNITY DAN PROFITABILITY TERHADAP CASH HOLDING DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI - Desy; Maran (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to examine the relationship between growth opportunities and profitability with cash reserves, with firm size as a moderating variable. This study is motivated by the phenomenon of differences in corporate strategies in managing cash reserves, particularly in the post-COVID-19 pandemic period, which is characterized by high global uncertainty. This study uses a quantitative approach, using a sample of 67 industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2024 period based on certain criteria. This data was tested using panel data regression analysis using EViews 13 and Moderated Regression Analysis (MRA). Data analysis shows that growth opportunities have an inverse (negative) and significant relationship with cash holdings. Profitability has a unidirectional (positive) and significant relationship with cash holdings. Meanwhile, company size, which is expected to act as a moderator, has been shown to have no significant impact in strengthening or weakening the relationship between growth opportunities and profitability with cash reserves. In other words, the size of a company does not directly determine how the relationship between these variables is formed